ETNOMATEMATIKA DALAM MERANGKAI MANIK MASYARAKAT DAYAK KAYAAN KAPUAS HULU - Haran, Agustina; Hartoyo, Agung; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMathematics at school and mathematics found by students in everyday life are very different. That is why, mathematics is often seen as a difficult lesson by students. Mathematics must build a bridge between real-world mathematics and mathematics at school. This study aimed to identify elements of Dayak Kayaan beads that are related to mathematics. The subject of this study was those who considered to have the required knowledge, namely FeronikaBuaa, EmilianaKavung, and Klara Ida. The method used in this study is a qualitative descriptive method. From the results of interviews and analysis of the data obtained are (1) How to mention the calculation of beads related to the material spelled; (2) The drawing pattern on the bead sequence is related to square material (flat build); (3) Grouping of bead colors on bead sequences related to set material; (4) Economic Value related to social arithmetic; (5) Forming a pattern with an odd bead in a series of beads related to the material of odd numbers; (6) The similarity of the shape of the drawing pattern to the bead sequence is related to the material of symmetry.Â Keywords: Ethnomathematics, Stringing Beads, Dayak KayaanÂ